Variability in plasma concentrations of methylprednisolone 6 days after intrasynovial injection of methylprednisolone acetate in racing horses: A field study. (5th September 2018) - Machin, J.; Duer, W.; Maylin, G.; Fenger, C.; Wilson, D.; Ivey, M.; Berthold, B.; Allison, S.; Tobin, T.
Summary: Background: Methylprednisolone (MP) acetate is a commonly used corticosteroid for suppression of inflammation in synovial structures in horses. Its use is often regulated in equine sports by plasma MP concentrations. Objectives: To describe variability in MP plasma concentrations after MP acetate injection in different synovial structures and with co‐administration with hyaluronic acid (HA). Study design: Field study in actively racing horses in three disciplines (Thoroughbred, Standardbred and Quarter Horse). Methods: Seventy‐six horses (15 Thoroughbreds, 20 Standardbreds and 41 Quarter Horses) were included in the study. Injection of any synovial structure with a total body dose of 100 mg MP acetate was permitted, data were grouped according to the synovial structure injected and co‐administration with HA. Plasma was collected before injection and at 6 days post‐injection. Per cent censored data (below the limit of quantification) for each synovial structure were determined, and summary statistics generated by Robust Regression on Order. Differences between synovial structures and co‐administration with HA were identified by ANOVA with Tukey's post hoc testing. Results: The MP plasma concentration at 6 days for injection for the entire group (mean ± standard deviation [s.d.], pg/mL) was 96 ± 104. Metacarpophalangeal (MCP) plasma concentrations contained 86% censored data and could not be included in the statistical analysis. The carpal joints (CJO) group had a lower plasma MP concentration (P<0.05) than the distal tarsal joints (DTJ) or medial femorotibial (MFT), the no HA (NHA) group had a lower plasma MP concentration (P<0.05) than HA. Main limitations: The synovial structures injected varied by racing discipline, so this study was unable to identify any differences between disciplines. Conclusions: Practitioners should be aware that injection of DTJ, CS and MFT joints, and combining MP acetate with HA may prolong its clearance, and withdrawal times for competition in regulated equine sports.